The Comparison between Consumption and Production-based Zakat Distribution Programs for Poverty Alleviation and Income Inequality Reduction - Qurroh Ayuniyyah; Ataul Huq Pramanik; Norma Md Saad; Muhammad Irwan Ariffin (Center of Strategic Studies (PUSKAS) BAZNAS, 2017)
This study attempts to analyze the effect of consumption and production-based zakat distribution programs in eradicating poverty and reducing income inequality of the zakat beneficiaries by using the modification of the Center of Islamic Business and Economic Studies (abbreviated as CIBEST) model, Deciles method, Gini coefficient and Atkinson index. It takes the case study of 1,309 zakat beneficiaries managed by the National Zakat Board of Indonesia (abbreviated as BAZNAS) in three different cities and regencies including Bogor, Depok and Sukabumi. It suggests that the present zakat distribution programs conducted by BAZNAS can significantly alleviate poverty and reduce income inequality among zakat beneficiaries. It is observed that one year after receiving zakat programs, production-based programs have higher increase of the material and spiritual condition (represented by falah index) by 300 percentage points while households who obtained consumption-based programs rise by only 20 percentage points. It is also found that the Gini coefficient decreases by 0.017 points while Atkinson index falls by 0.042 points indicating that the income inequality among observed zakat beneficiaries are improved. This study has substantiated the role of zakat for poverty alleviation and income inequality reduction that can benefit development in general. Keywords: Zakat Distribution Programs, Poverty, Income Inequality